Prevalence and Predictors of Non-Benzodiazepine Use in Patients with Alcohol Withdrawal Syndrome in United States Emergency Departments - a cross-sectional study - Kirolos Zakhary; Sophia Bruno; Caleb Myatt; Vindya Perera; Kerolese Saleh; Jacob Smearman; Madeline Yuzwa; Mate Soric; Stephanie Zampino (University of Minnesota Libraries Publishing, 2024)
Purpose: Benzodiazepines are the mainstay treatment in Alcohol Withdrawal Syndrome (AWS), though they have the potential for abuse and cognitive side effects. Non-benzodiazepines are of growing interest for treatment of AWS; however, the prevalence of non-benzodiazepine use remains unknown. The purpose of this study is to evaluate the prevalence and predictors of non-benzodiazepine use for AWS in the Emergency Department (ED). Methods: A cross-sectional, retrospective study utilizing data from the National Hospital Ambulatory Medical Care Survey (NHAMCS) spanning the years 2014-2020 investigated patients presenting to the ED with AWS. The primary outcome of this study is the prevalence of patients with AWS who received non-benzodiazepine treatment during their ED visit. The secondary outcome was the identification of predictor variables for non-benzodiazepine use. A multivariate logistic regression with a backward elimination approach was employed to identify predictor variables. Results: A total of 2,300 unweighted ED visits included over the study years. When weighted, this represented over 15.2 million ED visits. Across the study period, 3.1% (95% CI, 1.6-6.1%) of patients received non-benzodiazepines. Positive predictors of non-benzodiazepine use included the year 2020 compared to 2014 (OR 6.32, 95% CI, 1.39-28.73) and comorbid depression (OR 4.13, 95% CI, 1.38-12.36). Negative predictors of non-benzodiazepine use included ages 18-40 compared to ages 41-64 (OR 0.34, 95% CI, 0.13-0.91), nursing home residence compared to private residence (OR 0.02, 95% CI, 0.001-0.80), and the South compared to the Midwest region of the United States (OR 0.19, 95% CI, 0.07- 0.51). Conclusion: This study found that non-benzodiazepine use, despite being less common, is becoming more prevalent. Further research is needed to determine the optimal dosing and duration of non-benzodiazepines for AWS. Understanding the factors influencing the prescription patterns of non-benzodiazepines can contribute to informed decision-making and improve the management of AWS.